Antimicrobial properties of tetracycline and minocycline-montmorillonites - Parolo, Maria Eugenia (2010)
The antimicrobial activity of adsorption complexes of antibiotics from the tetracycline family on sodium and calcium montmorillonite was evaluated for their use in human and veterinary medicine. Tetracycline (TC) and minocycline (MC) adsorption on Patagonian montmorillonite was studied as a function of pH using batch experiments, X-ray diffraction (XRD) and IR spectroscopy. The adsorption was high at low pH and decreased continuously as pH increased. Adsorption of MC was higher than adsorption of TC. TC and MC were intercalated into the interlayer space of montmorillonite as deduced from the increase of the basal spacing. IR spectroscopy suggested that NHR3+ and other polar groups were directly involved in the interaction with montmorillonite. The antimicrobial activity, measured by inhibition tests, was maintained by the antibiotics after adsorption on montmorillonite, whereas unreacted montmorillonite did not show any antibacterial activity. The excellent activity shown by the TC and MC complexes provides a promising field of application, in particular for the formulation of topical products.